ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN DI KECAMATAN WONOTUNGGAL KABUPATEN BATANG - Fatkhus Solikhati; Farida Sukowati; Sri Sumarni (JURNAL KEBIDANAN, 2018)
According to Indonesia Demographic and Health Survey 2014 exclusive breastfeeding coverage only reached 52.4%, in Central Java at year of 2014 exclusive breastfeeding coverage reached 57.6%, in Batang Regency at year of 2015 exclusive breastfeeding coverage of 52.67%, and in Wonotunggal sub-district of Batang Regency In the year of Year 2015 exclusive ASI coverage of 42.1%. The presentage of it is still below of the target set in the Minimum Service Standards of 80%. This shows that exclusive breastfeeding is still low.This study aims to determine the relationship between the level of knowledge, employment status, family support and the support of health workers with exclusive breastfeeding in Sub District Wonotunggalof Batang Regency. The research method used analytical survey with cross sectional approach. The sample of this research is all breastfeeding mothers who have babies aged 7-8 months in Sub District Wonotunggal of Batang Regency as many as 86 mothers which is the total population. Data collection using questionnaire, statistic test used is Sperman Ro test and Chi_square test. The results showed that 60.5% of mothers had a good level of knowledge, 72.1% of mothers did not work, 52.3% of families supported, 50% of health workers supported, and 60.5% gave exclusive breastfeeding to their babiesthere was a correlation between maternal knowledge level (p = 0,001), family support (p = 0,001) and support of health workers (p = 0,001) with exclusive breast feeding but no relation between maternal status (p = 0,457) exclusive breast feeding in Wonotunggal sub-district, Batang regency. From the results of this study is expected that families and health workers play an active role in supporting exclusive breastfeeding and as input for health agencies associated with factors that cause the low coverage of exklusive breastfeeding.